On the possibility of neoplastic growth of the descemet's corneal endothelium - Артьомов, Олександр Валентинович (My University, 2026)
Background: The tumor process inside the eye covers most of the inner perimeter: from the iris to the optic nerve head. At the same time, there is a little information about neoplastic changes of Descemet’s endothelium although the cells of this tissue prone to proliferation and pathological tissue growths. Aim: To present a histomorphological picture of unusual proliferation of the Descemet's endothelium, which had some signs of a neoplasm. Materials and Methods: The histomorphological picture of a unique pathological process was studied in 40 serial sections of the eyeball. The histological picture was compared with the clinical one. Results: Histomorphological examination revealed obliteration of the iridocorneal angle with fibrosis-hyalinosis of the drainage zone and neoplastic changes inside the eye: a cavernous hemangioma, neoplastic complexes of flattened round-oval non-pigmented cells in the zonule of Zinn, in the anterior chamber, on the anterior surface of the iris and identical cell complexes along the surface of Descemet's membrane. Conclusions: For the first time, emphasis was placed on the possibility of a neoplastic process in the endothelium of Descemet's membrane, the implementation of which is extremely difficult due to the absence of a stromal-vascular pool in this tissue system.
Keywords: posterior corneal epithelium; neoplastic proliferation; ntraocular tumors; cornea